2009
DOI: 10.1007/s00213-008-1452-9
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of sarizotan into the subthalamic nucleus attenuates levodopa-induced dyskinesias in 6-OHDA-lesioned rats

Abstract: These results suggest that the STN is a target structure for the antidyskinetic action of sarizotan and indicate that drug-mediated modulation of STN activity may be an alternative option for the treatment of levodopa-induced dyskinesias in Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 67 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…Those data suggest different pathophysiological mechanisms underlying L-DOPAinduced and dopamine agonist-induced dyskinesia or an additional site of action of 5-HT 1A agonists within the basal ganglia circuit, for instance the thalamocortical synapse (Huot et al, 2011b). The STN might well be another site of action of 5-HT 1A agonists, as suggested by a study conducted in the 6-OHDA-lesioned rat in which injection of the nonselective 5-HT 1A agonist sarizotan in the STN alleviated LI-AIMs (Marin et al, 2009b). However, an intra-STN site of action is hard to reconcile with the classic model of the basal ganglia, as it would ultimately disinhibit glutamatergic thalamocortical transmission, thereby exacerbating LID, yet a reduction was observed experimentally.…”
Section: A 5-ht 1a/1b Receptorsmentioning
confidence: 98%
“…Those data suggest different pathophysiological mechanisms underlying L-DOPAinduced and dopamine agonist-induced dyskinesia or an additional site of action of 5-HT 1A agonists within the basal ganglia circuit, for instance the thalamocortical synapse (Huot et al, 2011b). The STN might well be another site of action of 5-HT 1A agonists, as suggested by a study conducted in the 6-OHDA-lesioned rat in which injection of the nonselective 5-HT 1A agonist sarizotan in the STN alleviated LI-AIMs (Marin et al, 2009b). However, an intra-STN site of action is hard to reconcile with the classic model of the basal ganglia, as it would ultimately disinhibit glutamatergic thalamocortical transmission, thereby exacerbating LID, yet a reduction was observed experimentally.…”
Section: A 5-ht 1a/1b Receptorsmentioning
confidence: 98%
“…Although the expression of D 4 R in striatal neurons is controversial (Fishburn et al, 1995;Matsumoto et al, 1996;Rivera et al, 2002;Suzuki et al, 1995), the selective inhibition of D 4 R reduces LID in the MPTP monkey (Huot et al, 2012a), and sarizotan, a D 4 R antagonist and 5-HT 1A receptor agonist, has been shown to reduce LID in both rat and non-human primate models (Grégoire et al, 2009;Marin et al, 2009), as well as in PD patients in clinical trials ( Bara-Jimenez et al, 2005;Olanow et al, 2004). However, this clinical result was not confirmed in a placebo-controlled phase III study (Goetz et al, , 2008.…”
Section: The Dopaminergic Systemmentioning
confidence: 98%
“…Pharmacology Dyskinesia Impulsivity and addictions Dopaminergic and/or serotonergic system Sarizotan D2-like receptor antagonist and 5-HT 1A agonist in 6-OHDA rat and MPTP monkey (Grégoire et al, 2009;Marin et al, 2009) Buspirone 5-HT 1A partial agonist and D2-like receptor antagonist in 6-OHDA and MPTP rodents (Dupre et al, 2007(Dupre et al, , 2008Eskow et al, 2007Eskow et al, , 2009Kannari et al, 2001;Lundblad et al, 2005;Tomiyama et al, 2005) impulsivity after acute treatment and impulsivity after chronic treatment in rat (Lu et al, 2013) methamphetamine and cocaine reinstatement in rat (Shelton et al, 2013) Tandospirone 5-HT 1A partial agonist impulsive choice in rat (Ohmura et al, 2013) Quetiapine 5-HT 2A antagonist, D2-like receptor antagonist, adrenergic antagonist in 6-OHDA rat and MPTP monkey (Oh et al, 2002) impulsivity at a high dose in rat (Amitai and Markou, 2009 Non-selective opioid receptor antagonist suppresses ethanol-induced behaviors in alcohol preferring rat (June et al, 2004) GABAergic system Topiramate GABA A agonist in MPTP monkey (Silverdale et al, 2005) and synergistic effect with amantadine in 6-OHDA rat (Kobylecki et al, 2011) Voluntary alcohol intake in alcohol high preferring rats (Johnston et al, 2010;Savola et al, 2003) Propanolol ␤1/␤2 receptors antagonist in 6-OHDA rat and MPTP monkey (Dekundy et al, 2007;Gomez-Mancilla and Bedard, 1993) different substances induced abnormal behaviors (impulsivity, conditioned place preference. .…”
Section: Drugmentioning
confidence: 99%
“…They also exhibit modest agonist properties at 5-HT 1A receptors (Newman-Tancredi et al, 1998), so interpretation of their effects is complex. Any of these non-5-HT 2A actions could be responsible for the loss of antiparkinsonian (Lejeune et al, 1997); E max , 101% (Cornfield et al, 1991) Buspirone Reduces AIMs, impairs rotarod performance, this latter action may reflect loss of antiparkinsonian benefit (Dekundy et al, 2007) Reduces dyskinesia, but worsens parkinsonism (Ludwig et al, 1986;Bonifati et al, 1994) K i , 20 nM (Hamik et al, 1990); E max , 22% (Dupuis et al, 1999) Sarizotan Reduces AIMs (Marin et al, 2009) Reduces dyskinesia and L-DOPA antiparkinsonian benefit at high dose (Gregoire et al, 2009) Reduces dyskinesia (phase II) (Olanow et al, 2004), reduces dyskinesia compared with baseline, but not compared with placebo (phase III) (Goetz et al, 2008), no dyskinesia reduction and worsening of parkinsonism (phase III) (Goetz et al, 2007) K i , 2.2 nM (Newman-Tancredi et al, 2005); E max , 100% (Bartoszyk et al, 2004) Tandospirone Reduces dyskinesia, but worsens parkinsonism (Kannari et al, 2002) K i , 27 nM (Hamik et al, 1990); E max , 67% (Tamaoki et al, 2007) Anatomically Selective Therapies for Parkinson's Disease efficacy, and it could be argued that even the antidyskinetic actions of these compounds have little to do with 5-HT 2A antagonism. However, a PET study performed in schizophrenic patients demonstrated that at doses used to treat PD motor and nonmotor complications clozapine leads to greater 5-HT 2 than D 2 -like receptor occupancy (Nordström et al, 1995).…”
Section: -Ht 1a Agonist R-(ϩ)-8-oh-dpatmentioning
confidence: 99%